2022
DOI: 10.1155/2022/7511345
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Galangin Methylation Modification Based on Cell Imaging on Inflammatory Lung Injury and Its Molecular Mechanism

Abstract: Background. Recently, inflammation has become a major threat to human health. Studies have confirmed that some Chinese traditional medicine ingredients may effectively interfere with the expression of inflammatory mediators through epigenetic modification, showing a great potential of the application. Objective. To investigate the role of the PPAR/DNMT3A pathway in the reversal of galangin-mediated inflammatory lung injury, promote the development of new anti-inflammatory drugs, reduce the side effects of chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Therefore, the PPAR/DNMT3A pathway is considered the main molecular mechanism involved in reversing inflammatory organ damage by alpinetin. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the PPAR/DNMT3A pathway is considered the main molecular mechanism involved in reversing inflammatory organ damage by alpinetin. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that PPAR activation induced by alpinetin can further promote the synthesis and modification activity of DNA methyltransferase DNMT3A in the nucleus of RAW 246.7 (the macrophage cell line), thus promoting the methylated modification of the IL‐6 promoter and blocked the binding of transcription factors. Therefore, the PPAR/DNMT3A pathway is considered the main molecular mechanism involved in reversing inflammatory organ damage by alpinetin 14,15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation